MEASURING THE PERFORMANCE OF INDUSTRIALISED BUILDING SYSTEM (IBS) CONSTRUCTION PROJECT TOWARDS ACHIEVING GREEN CONSTRUCTION IN MALAYSIA - MAT ISA, SITI SARAH; WAN ISMAIL, WAN NORIZAN; ZAINAL, ZAIWANNIZAR; MD ZAIN, NORAINI (Human Sustainability Procedia, 2018)
The Malaysian government is committed to change significantly through embracing sustainable practices and meeting its target and obligations towards sustainable development. In respond to these desires, Industrial Building System (IBS) and their design procedures are considered as an opportunity to introduce sustainable features to the construction process and enhance construction sustainability into a more socially responsible, environmentally sustainable and economically viable to meet current demand of the construction market. This research mainly study the fundamental connotation of IBS that has the potential contributing to green construction and illuminates the significance and meaning of green construction principles based on IBS perspectives. The establishment of effective methods to evaluate the performance of different approaches in which IBS contributes to green construction is crucial for better understanding by construction organisation at present in deliberate whether returns have beenattained on their investment in implementing IBS in construction project